Rentabilidad del Cultivo de Almizcle (Abelmoschus spp) en pequeños productores de la provincia de Lamas, región San Martín - Azang Huamán, Pompilio (2015)
The present research titled " Profitability of the crop of Ambretta plants (Abelmoschus Spp) in small producers of the province of Lamas, region of St Martin ", obeys to develop the sector of Ambretta and to answer better to the requirements of the producers, and businessmen of this local and global society. The present work is developed with San martin national university - Tarapoto, postgraduate school, postgraduate section of the faculty of economic sciences, for which there has been identified and prioritized Pamashto's community, province of Lamas, for being experienced with this growing; for which a set of surveys have been realized with the producers of Ambretta plants, and information was searched in the public and private institutions dedicated to this activity. The Analysis of Study was done on the basis of the variables: Profitability of the Ambretta plants, by means of the indicator of clear benefit. Cost of production by means of the indicator of average cost. And Productivity by means of the productivity performance per Hectare (Kilograms per Hectare). The results of the study indicate the sample taken of the population of producers of Ambretta plants in Pamashto's community. The variables are significant to 5 % of significancy, as well as in the test of F, it indicates that the used variables are the suitable ones. We conclude that the most important variables that influence the profitability of the culture of Ambretta plants are: -The costs of production. -The productivity. With the profitability, by means of benefit / clear cost indicator, it can be observed that for every unit there is an improvement of five and 29/100 units for agricultural campaign of Ambretta plants.